The Social Meaning Potential of the Global English Based on Data from Different Communities - Vaicekauskienė, Loreta (Taikomoji kalbotyra, 2020)
This paper describes the social value of the global English language as identified in the investigations of various communities worldwide and shows how the social meanings of English relate to each other in a broader ideological field universal for today’s locally global world. The notions of indexical field (Eckert 2008) and bivalent indexicality (Cotter, Valentinsson 2018) are applied in the analysis. The aim of the study is to synthesize results obtained by different researchers from different ideological and communicative contexts and to explore the indexical potential of English, including its local varieties and mixed speech styles. The study is based on a qualitative analysis of a corpus of secondary sources, consisting of a total of 74 scholarly publications from the Expanding Circle communities, which were published in English in 1990–2020 (most of them during the second decade of the 21st century). In total, more than 50 social meanings of the global English language have been identified. It is likely that the abundance of social associations with English is due to the strong first-order indexes. Hence, the social meanings were grouped into the following nine indexical categories based on the presumed first-order sociocultural indexicalities: British and American culture; International sphere; Technologies, science and education; Economic and social status; Personal capital; Youth; Popular culture and media; Urban sphere; and Male. Positive social meanings dominate the indexicalities, but for some of them, bivalent indexicality (presence of contradictory positive and negative values) has been recorded. Although there is much overlap between these relative categories, the constellation as a whole is interpreted as a complex of several separate and multivalent indexical fields. It is to be hoped that this study not only illustrates that the notion of indexical field is applicable for analysis of the imagined global community of users of English, but also provides a broader ideological context for further research of the social meaning-making potential of the global English language.